Chlamydial infection among patients attending STD and genitourinary clinics in Taiwan - Chen Shou-Chien; Chen Kow-Tong; Chiang Chien-Chou; Li Lan-Hui; Tang Li-Hui (BMC, 2007)
Abstract Background The main objective of this study is to examine the epidemiology of Chlamydia trachomatis (CT) infection amongst patients (473 men, 180 women) seen two hospitals in Taiwan. Methods Between July 2004 and June 2005, a total of 653 patients provided first-void urine samples for examination of CT using PCR assay. Results The overall prevalence of CT infection was 18.4% (95% confidence interval [CI] 17.3-19.5). Prevalence for men and women were 16.7 % (95% CI 15.3-18.0%) and 22.8% (95% CI 17.5-28.1%), respectively. Age group-specific prevalence was 25.7% (95% CI 22.5-28.9%) in < 20 year olds, 23.5% (95% CI 20.3-26.7%) in 20-24 year olds, 22.3% (95% CI 18.9-25.7%) in 25-30 year olds, and 11.5% (95% CI 10.3-12.7%) in > 30 year olds. Independent risk factors for chlamydial infection included younger age (aged ≤ 30 years) (adjusted odds ratio [AOR] = 2.44; 95% CI 1.52-3.84; p < 0.001), inconsistent condom use (AOR = 2.01; 95% CI 1.32-3.06; p < 0.001), being symptomatic (dysuria, urethral discharge) at the time of testing (AOR = 1.84; 95% CI 1.21-2.80; p < 0.001), and having N. gonorrhoeae infection (AOR = 3.82; 95% CI 2.20-6.58; p < 0.001). Conclusion Genital chlamydial infection is an important sexually transmitted disease in Taiwan. Young Taiwanese persons attending a STD clinic should be screened for CT infection and counselled on condom use.